Ultrastructural Characterization of Human Oligodendrocytes and Their Progenitor Cells by Pre-embedding Immunogold - Ulloa-Navas, María J.; Pérez-Borredá, Pedro; Morales-Gallel, Raquel; Saurí-Tamarit, Ana; García-Tárraga, Patricia; Gutiérrez-Martín, Antonio J.; Herranz-Pérez, Vicente; García-Verdugo, Josée M. (Frontiers in Neuroanatomy, 2021)
Oligodendrocytes are the myelinating cells of the central nervous system. They provide trophic, metabolic and structural support to neurons. In several pathologies such as multiple sclerosis these cells are severely affected and fail to remyelinate, thereby leading to neuronal death. The gold standard for studying remyelination is the g-ratio, which is measured by means of transmission electron microscopy (TEM). Therefore, studying the fine structure of the oligodendrocyte population in the human brain at different stages through TEM is a key feature in this field of study. Here we study the ultrastructure of oligodendrocytes, its progenitors and myelin in 10 samples of human white matter using 9 different markers of the oligodendrocyte lineage (NG2, PDGFRa, A2B5, Sox10, Olig2, BCAS1, APC (CC1), MAG and MBP). Our findings show that human oligodendrocytes constitute a very heterogeneous population within the human white matter and that its stages of differentiation present characteristic features that can be used to identify them by TEM. This study sheds light on how these cells interact with other cells within the human brain and clarify their fine characteristics from other glial cell types.